Development of Web-Based Advertisement Media on Sahrul Home Car Care - Bakhtiar, Yohan; Izzah, Abidatul; Cinderatama, Toga Aldila; Nugroho, Benni Agung; Susanto, Riswan Eko Wahyu (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
Amidst the ongoing Covid-19 pandemic, non-essential activities have shifted mainly to the safety of people's homes. This includes remote work (Work From Home) and shopping for basic needs online. However, service workers, particularly those in the service sector like Muhammad Sahrul, have faced significant challenges navigating the pandemic's impact. Sahrul, who owns an all-brand car repair shop, experienced a decline in customers visiting his workshop due to the outbreak. Recognizing the need for a fresh approach, Sahrul created